Financing for development : (OPEC Fund for International Development, 2002)
All developing countries are, in principle, eligible for OFID assistance, although the least developed countries are given higher priority and have received more than one-half of the institution’s cumulative commitments to date. Also eligible are international institutions whose activities benefit the developing countries. OFID Member Countries are excluded from benefiting from assistance, except in the case of disaster relief or within the context of a regional program. Over the years, OFID has spread its presence to 134 countries, of which 53 are in Africa, 43 in Asia, 31 in Latin America and the Caribbean, and 7 in Europe.